Screening for creatine transporter deficiency in autism spectrum disorder: a pilot study - Arslan Mutluay; Yildiz Yılmaz; Olgaç Asburçe; Hekim Özlem; Yücel Çiğdem; Sertoğlu Erdim (Türk Biyokimya Dergisi)
Investigation of inherited metabolic disorders in autism spectrum disorder (ASD) is a matter of debate. X-linked creatine transporter deficiency is among the metabolic disorders which may present predominantly with features of ASD and intellectual disability. Here, we aimed to screen for creatine transporter deficiency in boys with ASD at a university hospital in Turkey.